Relics And Innovation In The Bawean, Sampang, And Rembang Dialects (A Collaborative Linguistic And Archaeological Study) (Journal of Namibian Studies : History Politics Culture, 2023)
This collaborative linguistics and archeology research takes the Bawean and Sampang dialects of Madurese, as well as the Rembang dialect of Javanese, as its research objects. It tests the hypothesis that these dialects are initial stopover places for Austronesian speakers in their post-Kalimantan and Sulawesi migration into the speech areas of Java and its surroundings. As noted by Bellwood, Bawean, Sampang, and Rembang—identified as important by Collins and Blust—have artifacts that show their historic role in the migration of Austronesian speakers to Java and its surroundings. This research investigates two research questions. First, did the post-Kalimantan and Sulawesi migration of Austronesian language families to Java Island and its surroundings originate around Bawean Island and the northern coast of Rembang? Second, to what extent does the evidence provided by linguistic features such as relics and innovations strengthen the hypothesis? This mixed methods research analyzed both linguistic features and archaeological evidence. Data were obtained by interviewing speakers of the dialects using questionnaires regarding their basic vocabulary, cultural vocabulary, movement, and verbs. Archaeological evidence in the three areas was also explored in a prefatory manner. Linguistic features were found in the form of relics, both in the speech areas of the Bawean and Sampang dialects of Madurese and the Rembang dialect of Javanese. It is concluded that post-Kalimantan and Sulawesi Austronesian speakers' migration to Java and its surroundings stopped at Bawean in the east and Rembang in the west. This was confirmed by artifacts, including stone graves in Bawean as well as vessels, kettledrums, and graves in Rembang.